The autonomy of public health facilities in decentralised contexts: insights from applying a complexity lens in Kenya. Issue 11 (14th November 2022) - Barasa, Edwine; Nyawira, Lizah; Musiega, Anita; Kairu, Angela; Orangi, Stacey; Tsofa, Benjamin
Abstract : The financing of public health facilities influences their performance. A key feature that defines health facility financing is the degree of financial autonomy. Understanding the factors that influence public health facility financial autonomy is pertinent to developing strategies to addressing challenges that arise from constrained autonomy. In this paper, we apply a complexity lens to draw on a body of research that we have conducted in Kenya over the past decade, from the onset of devolution reforms, to unpack the determinants of public health facility financial autonomy in a context of decentralisation and provide suggestions for pertinent considerations when designing interventions to address financial autonomy challenges. We find that the factors that affect public health facility autonomy are not only structural, but also procedural, and political and interact in complex ways. These factors include; the public finance management (PFM) laws, sense-making by actors in the health system, political interests in control over resources, subnational level PFM capacity, PFM implementation bottlenecks and broader operational autonomy. Drawing from this analysis, we recommend that efforts at resolving public health facility financial autonomy include: PFM capacity development for subnational levels of government in decentralised settings, the use of a political lens that recognises interests and seeks to align incentives in engagement and solution finding for health facility financial autonomy, the audit of PFM processes to establish and resolve implementation bottlenecks that impinge on public health facility autonomy, and the resolution of operational autonomy to as a facilitator of financial autonomy.